(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
The liver ( Latin, ancient Greek – hepar ) is not an integral part of the gastrointestinal tract (gastrointestinal tract), but is part of the digestive system. In addition to digesting food, the liver performs other vital functions. In our body, the liver is the largest gland. Its weight in an adult is 1300-1800 g. The liver is located in the upper abdominal cavity. Most of the organ is located to the right of the median vertical axis of the body. And only a small fragment goes to the left of it.